ENCOURAGING SUNNAH PRAYER ROUTINES: A TEACHER'S STRATEGY TO IMPROVE STUDENTS' RELIGIOUS CHARACTER - Ahmad Farhan Fatah; Ferianto Ferianto; Ahmad Irfan; Afif Nurseha; Syamsuddin Syamsuddin (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study aimed to describe the strategies used by Islamic Education teachers in encouraging the practice of sunnah prayers and to analyze their contribution to the formation of religious character among students. This study used a descriptive qualitative approach, which aimed to gain an in-depth understanding of the learning process and the habit of worship in a natural context. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using Miles and Huberman's interactive model, which includes data reduction, data presentation, and conclusion drawing. The results of the study showed that the strategies used by Islamic Education teachers in practicing sunnah prayers are carried out in three stages, namely: (1) planning activities by setting a routine schedule and assigning roles to mentors; (2) practicing through exemplary behavior, spiritual motivation, and active student participation in congregational prayers; and (3) evaluation through reflection and assessment of student character development. The habit of performing sunnah prayers has been proven to have a positive effect on the formation of students' religious character, especially in terms of discipline, sincerity, responsibility, and spiritual awareness. The implications of this study confirmed that the habit of performing sunnah prayers was not only a ritual activity but also an effective pedagogical strategy in instilling religious values and strengthening spiritual culture in the madrasah environment.